Myanmar’s trajectory towards democratization : an analysis on the repercussions of the Rohingya crisis - Auni Haziqah Ghufran (2017)
The Rohingya crisis has long reached international news, yet their persecution continues. When it erupted in 2012, Myanmar was a military regime with no democratic values to uphold. However, in 2015, Myanmar held free elections for the first time. This paper discusses if its blatant human rights abuses will hinder its democratization process. Secondly, this paper analyses the factors that have led to Myanmar’s 2015 elections using the work of researchers such as Lipset (1959), Pevehouse (2002), Boix (2003), Przeworski (2009), and more. In the discussion section, this paper explains how and why blatant human rights abuses will indeed affect its democratization process, and the two factors – interference from the international community and an unequal income distribution – that had led to the election. This paper recommends that the international community assists the new government in ensuring that they are able to govern with limited interference from the military.